Contextual and individual determinants of tooth loss in adults: a multilevel study - Luana Leal Roberto; Marise Fagundes Silveira; Alfredo Mauricio Batista de Paula; Efigênia Ferreira e Ferreira; Andréa Maria Eleutério de Barros Lima Martins; Desirée Sant'ana Haikal (BMC, 2020)
Abstract Background Tooth loss represents a known marker of health inequality. The association between tooth loss and unfavorable socioeconomic conditions is evident when analyzed at an individual level. However, the effects of contextual characteristics on tooth loss need to be better investigated and understood. The objective of this study was to analyze tooth loss among Brazilian adults (35-44 years of age), in accordance with individual and contextual social characteristics. Methods This was a multilevel cross-sectional study with data from 9564 adult participants from the Brazilian Oral Health Survey - SBBrasil 2010. The dependent variable was the number of lost teeth and the independent variables were grouped into structural (socioeconomic & political context) and intermediary (socioeconomic position, behavioral & biological factors, and health services) determinants. Multilevel Hierarchical Negative Binomial Regression was conducted and the Mean Ratio (MR) was estimated. Results Brazilian adults lost a mean of 7.57 (95% CI 7.1-8.1) teeth. Among the contextual variables, the number of teeth lost was higher among residents of municipalities with high and medium/low Municipal Human Development Index (MHDI) and in municipalities that did not have public water fluoridation. Among the individual variables, dental loss was higher among those who declared themselves yellow/black/brown/indigenous, were older, who had lower income, who had never visited a dentist, who had used dental services for more than a year and those whose most recent visit to the dentist was due to oral health problems. On the other hand, dental loss was lower among adults with higher education levels and males. Conclusions The number of missing teeth was associated with unfavorable contextual and individual conditions, which reinforces the need to reduce social inequality and guarantee regular, lifetime access to dental services.